Currents nutritional practices of nutritionists in the management of type 2 diabetes patients at Public Health Centres in Padang, Indonesia - Puri, Ice Yolanda; Mohd Yusof, Barakatun Nisak; Abu Zaid, Zalina; Ismail, Amin; Haron, Hasnah; Lipoeto, Nur Indrawaty (Multidisciplinary Digital Publishing Institute, 2021)
(1) Background: The interest in nutrition practices and education is slowly gaining traction among Indonesian nutritionists. However, there is a lack of local studies that evaluate nutritional practices, especially in the management of type 2 diabetes (T2DM). This cross-sectional study aimed to determine the nutritional practices among nutritionists and the adequacy of the current practices in the management of Type 2 Diabetes Mellitus (T2DM) patients at the Public Health Clinic in Padang (PHC), Indonesia. (2) Methods: An online survey form was distributed to all the nutritionists (n = 50) involved in the management of T2DM patients in their daily practices at the PHC. Socio-demographic characteristics, the current practice of T2DM, the need for DM nutrition education, and an evaluation questionnaire on the Indonesian Non-Communicable Diseases guideline and the Public Health Centre guideline were captured in the survey. (3) Result: A total of 48 completed survey forms were received, providing a response rate of 96% from the recruited nutritionists. One-third (37.5%) of the respondents counselled between one and ten patients per day. Nearly half (41.7%) conducted a monthly follow-up session for the patients at their respective PHC in the previous three months. Each nutritionist educated five to ten T2DM patients. The most common nutrition education topics delivered included appropriate menus (89.6%) as well as the etiology and symptoms of T2DM (85.5%). Almost all the nutritionists (93.8%) used leaflets and about 35.4% used poster education. Around 70.8% of counseling sessions lasted 30 min and two-thirds (66.7%) of the sessions included nutrition education. Based on the results, about half (52.1%) of them claimed that T2DM patients were reluctant to attend individual nutrition education. One-fifth of them (20.8%) claimed that it was because the T2DM patients were not interested in the tool kits and materials used. (4) Conclusions: T2DM patients are reluctant to attend individual nutrition education due to uninteresting tool kits and materials.